Social exchange and common agency in organizations - Robert Dur; Hein Roelfsema (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the relation between formal incentives and social exchange in organizations where employees work for several managers and reciprocate a manager's attention with higher effort. To this end we develop a common agency model with two-sided moral hazard. We show that when effort is contractible but attention is not, the first-best can be achieved through granting autonomy of effort choice to employees and giving bonus pay to both managers and employees. When neither effort nor attention are contractible, an attention race' arises, as each manager tries to sway the employee's effort his way. While this may result in too much social exchange, the attention race may also be a blessing because it alleviates managers' moral-hazard problem in attention provision. Lastly, we derive the implications of these contract imperfections for optimal organizational design.
Keywords: D86; J41; M50; M54; M55; 330; Anreizvertrag; Leistungsmotivation; Agency Theory; Soziale Beziehungen; Theorie